Power line magnetic field deviations for three different definitions of current unbalance - Antic, Danka (JET on-line, 2019)
An estimation procedure of the public's exposure to the low-frequency magnetic field generated by overhead power lines, according to the international standards, implies measurement and an extrapolation. It is necessary to measure both the magnetic field around the lines and the current in the lines simultaneously. The extrapolation procedure implies the calculation of the maximum magnetic field that will occur when the line current achieves its maximum. The calculation relies on a proportion between the current in the power line and the magnetic field around the power line, which is valid only when the currents are balanced. Unfortunately, the standards do not cover the unbalanced cases. The relation between the current unbalance and magnetic field could improve the estimation procedure. In the literature, several different definitions of the current unbalance could be found. In this paper, a comparison of three different definitions of current unbalance and their relation to the deviation of a magnetic field are considered. The magnetic field is calculated in the vicinity of the bus bar. The same procedure could also be applied around overhead power lines. The definitions for the current unbalance used in this paper are derived from the existing definitions of the voltage unbalance. Only one of these three definitions considers phase unbalance. The relationships between current unbalance and the maximum deviation of the magnetic field are found to be proportional.
Keywords: dobava energije; magnetic field; magnetno polje; measurement; merjenje; power delivery; public exposure assessment